An Approach to Comparing Nations for Inclusion of Studies in Health-based Systematic Literature Reviews - Deonandan, Raywat; Schachter, Howard; Ly, Mylan; Lacroix, Denise; Moore, Ceri; Barrowman, Nicholas; Abdulkadir, Idil; Girardi, Alberta (Université d'Ottawa | University of Ottawa, 2012)
Background: To develop and demonstrate a systematic approach for comparing nations, for the purpose of deciding whether to include or exclude studies in a systematic review of a health research question pertinent to the Canadian population. Results: a template of nine criteria was developed, including both sociodemographic and systemic indicators, and was applied to 68 jurisdictions, of which 19 were deemed sufficiently comparable to Canada to be included in the review. Conclusions: Subsequent systematic reviews, regardless of which nation is ultimately the reference population, should employ a similar process, with indicators and characteristics specific to the research questions, to ensure that political, economic, historical or ethnic biases are not influencing the selection or rejection of relevant papers.
Keywords: methods; cross-cultural comparison; cross-cultural characteristics; internationality